AME annual conference 1993 (Thomas Telford, 1993)
Providing access to engineering content from the past, this is the proceedings of the Association of Municipal Engineers' annual conference held in 1993.
Keywords: Municipal engineering -- Congresses.; elektronické knihy; electronic books